Implementation empowering communities in small scale irrigation projects during Covid 19 Pandemic in Padang and Padang Pariaman District. Issue 1 (April 2021) - Adji, B M; Istijono, B; Ophyandri, T; HIdayat, B
Abstract: During the covid 19 pandemic, development, and economic growth were hampered, so the people's purchasing power decreased. To overcome this, especially in rural areas, the government combined the P3-TGAI Program (the Acceleration for Irrigation Water Usability Improvement) and the PKT (Cash for work) Program in empowering the community in one way to recovery community income due to the covid pandemic 19. This article presents the P3-TGAI program as an implementation of community-based engagement in empowering communities. P3-TGAI is part of the PKT Program in Padang City and Padang Pariaman District, during the covid pandemic 19, including the covid protocol 19, which was carried out during the project work. This research uses a literature review method to describe the P3-TGAI and PKT program. Descriptive statistics are used to identify the benefits of the programs for the community and the covid 19 protocol performed during project work. The results of the study were that, although the covid 19 protocol was not fully implemented, the program is useful in recovering the community income during the covid 19 pandemics.